Histological Studies on the Kidneys of Barbari Goat (Capra hircus) - Gautam, Vinay Kumar; Singh, Krishna Nand; Kumar, Mukesh; Singh, Nripendra; Nimgaonkar, Mayur Sudhirrao (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A histologicalstudy was conducted on the kidneys of six Barbari goats of either sex between the ages of 1.5 and 2 years. The microscopic  examinations showed the thick fibrous capsule consisted of two layers. Interstitial tissue contained network reticular fi bers which  extended from the capsule to the apex of the papilla. The proximal convoluted tubule was lined by simple truncated pyramidal cells  with a brush border. Its lumen was irregular, while the distal convoluted tubule, collecting duct, and thick segment of Henle’s loop  were lined by simple cuboidal epithelium. In contrast, the thin segment of Henle’s loop was lined with simple squamous epithelium.  The juxtaglomerular cells were present within tunica media of the preglomerular portion of afferent and efferent arteriole. The cells  forming macula densa were single-layered. The papillary duct is lined with simple columnar epithelium, which becomes transitional  before opening into the papilla.
Keywords: Barbari Goat; Histology; Kidney